HINT1 is involved in the behavioral abnormalities induced by social isolation rearing. (21st October 2015) - Dang, Yong-hui; Liu, Peng; Ma, Rui; Chu, Zheng; Liu, You-ping; Wang, Jia-bei; Ma, Xian-cang; Gao, Cheng-ge
Highlights: The SI rearing mice exhibited depression-like and aggressive behavior. HINT1 protein levels decreased in prefrontal cortex but increased in hippocampus. HINT1 may be a molecular conjunction of SI and neuropsychiatric disorders. Abstract: Social isolation (SI) rearing has been demonstrated to induce behavioral abnormalities like anxiety, impulsivity, aggression, and learning and memory deficits which are relevant to core symptoms in patients with some certain neuropsychiatric disorders. But the underlying pathophysiological mechanisms remain unclear. Recent studies have revealed HINT1 has close relation with diverse neuropsychiatric diseases. In this present study, the SI rearing mice exhibited depression-like and aggressive behavior. Besides, HINT1 protein levels decreased in PFC but increased in HIP. Based on the data obtained, we concluded that HINT1 is involved in the behavioral abnormalities induced by social isolation and exerts distinct roles in different encephalic regions.